THE FIRE RISK ANALYSIS OF MONGOLIA - Uuganbayar Enkhtaivan,; Urjin Odkhuu,; Sarantsetseg Bazarvaani, (International Journal of Innovative Technologies in Social Science, 2025)
In recent years, the frequency of fires has been on the rise due to climate change, urbanization, and population concentration, leading to escalating damage and losses. This study seeks to showcase the potential of mathematical modeling in assessing fire risk levels on a global scale, drawing on statistical analysis of fires across Mongolia. The findings can inform strategic planning for fire prevention and mitigation efforts, aiding in effective risk management.